Pemodelan Pencemaran Udara untuk Industri Kayu Lapis di Kabupaten Blitar - Jawwad, Muhammad Abdus Salam; Murti, Restu Hikmah Ayu; Novembrianto, Rizka (Al-Ard: Jurnal Teknik Lingkungan, 2022)
A research to model particulate emission was conducted in the plywood industry in Kendalrejo, Talun, Blitar Regency, East Java at an altitude of 273 masl. The industry already has an environmental pollution control unit, with an outlet through a chimney emitting an average emission of 0.14 g/s. The model simulation was carried out using AERMOD View software with data on wind direction and speed, solar radiation, temperature, clouds, and air pressure. The results show that the presence of the wood industry in Talun, Blitar Regency will have an impact on particulate emissions to areas in the east, southeast, west, and south, as the dominant wind direction. Dispersion modeling of particulate pollution with current conditions has resulted in dispersion with concentrations below the allowable limit in PP 22 of 2021. Modeling with several scenarios shows that the dispersion pattern can be maximized by increasing the chimney emission rate to 18 m/s, to minimize turbulence around the chimney and accelerate the reduction of particulate concentrations. Increasing the height of the chimney or increasing the diameter of the chimney will also affect the decrease in concentration in all directions so it becomes a recommendation that should be considered by the industry.